2008
DOI: 10.1289/ehp.10636
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination Disinfection By-Products and Risk of Congenital Anomalies in England and Wales

Abstract: BackgroundIncreased risk of various congenital anomalies has been reported to be associated with trihalomethane (THM) exposure in the water supply.ObjectivesWe conducted a registry-based study to determine the relationship between THM concentrations and the risk of congenital anomalies in England and Wales.MethodsWe obtained congenital anomaly data from the National Congenital Anomalies System, regional registries, and the national terminations registry; THM data were obtained from water companies. Total THM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 30 publications
6
69
2
Order By: Relevance
“…Few studies have been published on chlorinated water and respiratory congenital anomalies, but two studies found a significant positive association (Aschengrau et al 1993;Hwang et al 2002), whereas two did not (Chisholm et al 2008;Nieuwenhuijsen et al 2008).…”
Section: (B) Reproductive Outcomesmentioning
confidence: 95%
See 3 more Smart Citations
“…Few studies have been published on chlorinated water and respiratory congenital anomalies, but two studies found a significant positive association (Aschengrau et al 1993;Hwang et al 2002), whereas two did not (Chisholm et al 2008;Nieuwenhuijsen et al 2008).…”
Section: (B) Reproductive Outcomesmentioning
confidence: 95%
“…A number of studies have found statistically significant positive associations between THMs and neural tube defects (NTDs), one of the most studied groups of congenital anomalies (Bove et al 1995;Klotz & Pyrch 1999;Dodds & King 2001), whereas other studies have not found statistically significant associations (Dodds et al 1999;Magnus et al 1999;Källen & Robert 2000;Hwang et al 2002;Shaw et al 2003;Nieuwenhuijsen et al 2008) (table 2). Klotz & Pyrch (1999) found a statistically significant association between total THM (TTHM) levels in the water and NTDs, but not with levels of haloacetonitriles and HAA.…”
Section: (B) Reproductive Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, chlorine can also react with natural materials in the raw water to form disinfection by-products (DBPs) that are hazardous to health (White, 1992;WHO, 2004;Uyak et al, 2008). Some epidemiologic studies (IARC, 1991;WHO, 1996;Singer, 1999;Magnus et al, 1999;Nieuwenhuijsen et al, 2008) have shown an association between long-term exposure to disinfection by-products and increased risk of cancer and potential adverse reproductive effect. Trihalomethanes (THMs) and haloacetic acids (HAAs) are the most important groups of DBPs in chlorinated finished water.…”
Section: Introductionmentioning
confidence: 99%